Perbandingan Semantik Ṣadr, Qalb, Dan Lubb Dalam Al-Qur'an: Analisis Makna Dan Konteks - Abdullah Abdullah; Bashori Bashori (JURNAL ILMIAH NUSANTARA, 2025)
The Qur’an frequently employs the terms ṣadr, qalb, and lubb to represent the inner dimensions of human spirituality. This study aims to compare the semantic meanings of these three key terms and to construct their hierarchical relationship within the structure of Qur’anic spiritual consciousness. Using a library-based research method and the semantic approach developed by Toshihiko Izutsu, this study analyzes the network of meanings and conceptual interrelations among the terms based on their Qur’anic usage. The findings reveal that ṣadr serves as the initial gateway of the soul, receptive to either divine guidance or satanic whispers; qalb acts as a dynamic center of belief, doubt, and moral fluctuation; while lubb represents the purified intellect, reflecting the highest stage of spiritual awareness. These terms form a spiritual hierarchy that not only illustrates stages of faith development but also reflects the Qur’anic worldview of human nature. The study contributes to the advancement of Qur’anic semantic theory and provides a foundational model for further applied research in spiritual education and character development rooted in divine values.